Phenotypic and Genotypic Characterization of Patients with Retinitis Pigmentosa in a Tertiary Hospital in the Philippines - Tamilyn Chelsea C. Laddaran, MD, DPBO; Manuel Benjamin B. Ibanez IV, MD, DPBO; Marianne Grace P. Navarrete, MD (Philippine Journal of Ophthalmology)
Objectives: To determine the phenotypic and genotypic characterization of individuals with retinitis pigmentosa (RP), identify their genetic etiologies, and provide counseling to affected patients.